Ionic liquid electrolyte selection for high voltage supercapacitors in high-temperature applications - Bahaa, Ahmed; Alhammadi, Ayoob; Lethesh, Kallidanthiyil Chellappan; Susantyoko, Rahmat Agung; Bamgbopa, Musbaudeen O. (Frontiers in Chemistry, 2024)
Systematic analyses of electrolyte physicochemical properties are important to screen ionic liquids (ILs) and understand the electrochemical performance of supercapacitor electrolytes. This study harmonizes evaluating electrochemical performance and transport properties of 8 shortlisted ILs from 22 commercially available hydrophobic ILs toward achieving a ≥5 V supercapacitor capable of high- The density, viscosity, and ionic conductivity of the 8 ILs were measured between 278.15 and 373.15 K to confirm the effects of temperature and ion structure before electrochemical characterization. The [FSI] based ILs ([Pip 1, 3] [FSI] and [Pyr 1, 3] [FSI]) showed lower densities and viscosities compared to other ILs among the 8 based on [TFSI]. Consequently, the highest conductivity was obtained for [Pyr 1, 3] [FSI]. Cyclic voltammetry and impedance spectroscopy was performed on supercapacitors assembled with the 8 ILs as electrolytes between 298.15 -353.15 K. Conclusions from the twoelectrode supercapacitors using multi-walled carbon nanotubes showed the 6 most-applicable towards the targeted SC ≥5 V at high temperature are; [Pip 1, 3] [TFSI] (5.4 V), [Pip 1, 3] [FSI] (5 V), [N 111, 3][TFSI] (5.1 V), [N 111, 6] [TFSI] (5.2 V), [Pyr 1, 102] [TFSI] (5.2 V), and [Pyr 1, 5] [TFSI] (5.2 V).